Dampak Kemacetan di Jalan Tol Brebes Timur - Mustika Sari; Deslida Saidah; Endang Wahyuni (Institut Transportasi dan Logistik Trisakti, 2018)
The purpose of this research is to know the congestion on the street toll road users. The problem in this research is the congestion and its impact on the road users, and how the solution to the congestion on the Brexit toll during Lebaran holiday season 2016. Population The study was conducted at East Brebes toll gate where the researcher distributed questionnaires to 80 respondents by purposive sampling method. Data analysis techniques use validity and reliability, simple linear regression, correlation coefficient, determinant coefficient, and hypothesis test. The result showed that there was a positive influence between congestion (X) and road users (Y), road congestion variation due to other factors of 95.4% while the rest of 4.6% was determined by other factors. With the probability significance of 0.005 t table> t table, it is concluded that individually the variables of congestion can affect the variables of users of toll road.